Bingo game: hidden treasure among heap of woods (the effectivity of a game in improving students' vocabulary mastery) - Eka Alfrida Ermawati; Ely Trianasari (English, 2019)
Research in the context of English as a foreign language suggests the use of games in the teaching learning process, either as enforcement or as teaching variations to make students learn in more relax condition. Students in the beginning level of learning, including young learners, still need encouragement. Word games, as it is believed, have the advantages of creating a context which help students’ attention focus on the task in a relax situation. Students even do not realize that they are practicing the language while playing. From various games suggested to teach young learners, Bingo is the recommended one. Bingo game is one of word games usually played by children outside the classroom. This game is interesting and challenging. By doing some modification, this game can be used to teach vocabulary and create a context from the material given in the classroom with their daily life context that is described by pictures and words. Concerning the power possessed by Bingo game, the presents study aims to reveal the effectiveness of Bingo game for improving students’ vocabulary mastery of the third semester students of business management of tourism study program in State Polytechnics of Banyuwangi. Vocabulary is selected as the sub skill taught using Bingo game since based on the preliminary study done the students in this program claimed that they have difficulty in memorizing it. Classroom action research design will be employed to answer the research questions in this study. The result of this study shows that Bingo game was able to improve students’ vocabulary mastery. It was showed by the improvement got from the students score after Bingo game applied.